A critique of baby making supermarts: Surrogacy clinics in Kishwar Desai’s Origins of Love (2012) - Mehta, Aparna; Saraswat, Surbhi; Paul, Meenakshi F. (Research Journal in Advanced Humanities, 2022)
This paper explores the exploitation of commercial surrogates at the hands of the various stakeholders and agents of the fertility industry in Kishwar Desai’s novel Origins of Love (2012). It begins with a brief description of the advances in the field of infertility treatment and the tailored options of the Assisted Reproductive Technologies (ARTs) for conceiving a child. It then traces the practice of surrogacy in mythology and explores how it is different from present day surrogacy. It further points out why ARTs is preferred over adoption by prospective parents and how this preference has led to the emergence of fertility clinics as the new baby supermarts, from where the parents can ‘buy’ egg, sperm and customised babies. The paper also throws light on how this trend of baby shopping makes fertility clinics operate akin to any other commercial industry and how in the novel Desai has depicted the inherent flaws of this phenomenon of baby shopping. It critically examines the rapid expansion of Reproductive Tourism due to transnational commercial gestational surrogacy and the huge popularity of India as a surrogacy hub, as depicted in Desai’s novel. The paper illustrates how surrogacy not only involves exploitation of women’s reproductive capacity but also encompasses physical, emotional, psychological and economic exploitation. The paper ends with a scrutiny of the blatant violation of medical ethics in the field of ARTs and the potentially dangerous long-term implications that these technological advancements can have on women’s health and the society at large.